The importance of academic new ventures for sustainable regional development - Aleksandar Vekic; Vladimir akovic; Jelena Borocki; Włodzimierz Sroka; József Popp; Judit Olàh (Amfiteatru Economic Journal, 2020)
Establishment of new entrepreneurial ventures have a direct influence on economic growth of the economy and society of every country. It relates especially to unemployment level and net income of the employees. Given these facts, the two aims of the paper are: 1) presentation of the Innovativeness of 14 countries of South - East Europe region and two additional countries: Poland and Hungary based on their overall ranking(s) as well as Information and Communication Technologies, ICT access and ICT use; and 2) to present development and business performance of academic start-up and spin-off companies in ICT sector which were created by the University of Novi Sad (Serbia) and which allowed it to become a sustainable University. The indicators such as total number of new ventures, number of employees, total revenue and average gross profit margin were used in order to analyse establishment, development and sustainability of academic ICT start-up and spin-off companies. The study shows that sustainable measures, particularly academic start-up and spin-off companies, have a very important role in sustainable economic growth (local, national and regional) and are a significant driver of innovation. They are of key importance for the sustainable development of the University.
Keywords: L26; M13; M15; O30; Q55; 330; Global Innovation Index; Information and Communications Technologies; Innovation; Academic Start-up and Spin-off Companies; Sustainable Measures; Sustainable University